2010
DOI: 10.1016/j.jfms.2009.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous mycoflora and CD4:CD8 ratio of cats infected with feline immunodeficiency virus

Abstract: This study was designed to compare cutaneous mycoflora isolation and CD4+:CD8+ ratio in feline immunodeficiency virus (FIV)-infected cats with that in FIV-uninfected cats. Sixty cats were examined. Twenty-five were FIV-infected cats and 35 were FIV-uninfected cats. All 60 cats were FeLV-negative. Fungi were speciated and immunophenotyping of peripheral CD4+ and CD8+ T lymphocytes was performed. At least one fungal colony was isolated from 22/25 (88%) FIV-infected cats. Among the FIV-uninfected cats fungal colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 19 publications
2
12
0
2
Order By: Relevance
“…Their incidence depends on geographical regions, cat subpopulations (pet, indoor, stray, feral, free-roaming, etc. ), gender and age [11,12,[16][17][18][19][20][21][22][23][24][25][26][27][28]. Incidence of other opportunistic microbes depends on endemic geographical areas and local vectors (e.g.…”
Section: The Feline Aids Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Their incidence depends on geographical regions, cat subpopulations (pet, indoor, stray, feral, free-roaming, etc. ), gender and age [11,12,[16][17][18][19][20][21][22][23][24][25][26][27][28]. Incidence of other opportunistic microbes depends on endemic geographical areas and local vectors (e.g.…”
Section: The Feline Aids Modelmentioning
confidence: 99%
“…Both FIV and FeLV independently might predispose animals for toxoplasma infection [21]. In spite of similar clinical manifestations by FIV or FeLV, they might specifically predispose the host for different heterologous microbial pathogens: FIV predisposes to Leishmania [12,16], mycoplasma [25,27,33,35], fungal [26], FCoV [12] infections, while FeLVsensitises the organism to BH infection [36]. Others found that the rate of toxoplasma [16,30,32] or FCV [24] infections occur independently of FIV status.…”
Section: The Feline Aids Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…No predisposing disorders were identified and the histopathological changes were nonspecific. In cats, Malassezia overgrowth has since been associated with retroviral infections [8,9], paraneoplastic syndromes [10,11], thymoma [11,12], and diabetes mellitus [13,14]. In a retrospective study, Maudlin et al evaluated the presence and importance of Malassezia yeasts in feline skin biopsy specimens submitted for histopathological examination between January 1999 and November 2000 [11].…”
Section: Discussionmentioning
confidence: 99%